The Effect of Leadership And Work Demands on the Performance of Lecturers and Educational Staff at Stikes Senior Medan 2021 - Sinaga, Sahat; Ferawati Artauli Hasibuan; Willy Cahyadi (IJCS: International Journal of Community Service, 2022)
Organizational leadership is the ability to influence a group towards the achievement of a goal, so that the creation of good leadership and low work stress in the organization can improve employee performance to achieve a goal. This study aims to determine the effect of leadership and work stress on the performance of lecturers and education staff at the Medan Senior High School of Health in 2021. This research is a quantitative study using a survey method, in which basic data from a sample of a population is collected using a questionnaire instrument in field. The data used in this study is primary data. Primary data is obtained directly from the original source through the distribution of questionnaires to respondents. The research population was all lecturers and education staff at the Medan Senior High School of Health as many as 50 people with the number of samples used as total sampling. Data collection techniques were carried out by interviewing and distributing questionnaires to respondents. Classical assumption test is done by normality test, multicollinearity test, heteroscedasticity test. The data analysis technique used the T-test and F-test. The results showed that the t-count value > t-table, namely the leadership t-count value 2,978 > 1.677 and the t-count compensation value 2,040 > 1,677, this indicates that there is a positive and significant influence between leadership and work stress. on the performance of lecturers and education staff. Meanwhile, it simultaneously shows that the calculated F value > F table (4,641 > 3,20).